Response to Growth and Yield of Chili (Capsicum annuum L.) to the application of biological fertilizers and Biochar - Nabilah Rizqiyah Rahma Dani; Yonny Koentjoro; Nova Triani (Universitas Wahid Hasyim, 2025)
Chili is one of the vegetable commodities that is often consumed by people in Indonesia. The demands of chili will increase along with population and industrial development in Indonesia. The rising demand for chili will increase the use of chemical fertilizers, especially Urea and NPK. Efforts to reduce the use of excess chemical fertilizers are to use biofertilizers and biochar. Biofertilizers function to provide nutrients to replace chemical fertilizers while biochar is a soil ameliorant material that can bind nutrients and water in the soil. The application of biological fertilizers and biochar is expected to improve the chemical, biological and physical properties of the soil so as to provide media and nutrients for plant growth. In addition, the purpose of this study was to obtain the best combination dose of biochar and biofertilizer on the growth and yield of red chili. This study used a factorial randomized group design (RAK). The first factor is the dose of biofertilizer (Y) consisting of 3 levels, namely 6 l/ha, 8 l/ha and 10 l/ha. The second factor is the dose of biochar (B) consisting of 4 levels, namely 6 tons/ha, 8 tons/ha, 10 tons/ha and 12 tons/ha. The results showed that the combination of biofertilizer doses and biochar treatments interacted with plant height at 28 and 35 HST (Days After Planting), number of leaves at 35 HST and fruit weight throughout the harvest period. The best combination was found at a dose of 6 l/ha biofertilizer and a dose of 8 tons/ha biochar. Keywords: growth and yields, chili, biochar, biofertilizers